Fidelizando la Fe: Estrategias de marketing relacional y comunidades de marca en la Hermandad de la Macarena - Berraquero-Rodríguez, Diego; Cristófol, Francisco Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This study analyzes how the Hermandad de la Macarena has evolved from a religious entity to a global corporate brand. Through relationship marketing and the concept of brand community, it examines its strategic management with members and stakeholders to generate shared value. Using a case study approach and diverse sources, key variables such as brand architecture, values and globalization are highlighted. The research shows how the Brotherhood has consolidated a solid and differentiated community, combining tradition and modernity, positioning itself as a benchmark among religious organizations.
Building Faith Loyalty: Relationship Marketing Strategies and Brand Communities in the Hermandad de la Macarena
Keywords: marketing relacional; comunidad de marca; redes sociales; marketing cofrade; Semana Santa; marca; relational marketing; brand community; social networks; brotherhood marketing; Holy Week; brand